Significance of an Early Repeat Troponin Measurement Upon Presentation to the Hospital for Acute Heart Failure - Yu Horiuchi; Alan S. Maisel; Dirk J. van Veldhuisen; Christian Mueller; Christopher Hogan; Michael C. Kontos; Chad M. Cannon; Gerhard A. Müller; Pam Taub; Gary M. Vilke; Stephen Duff; Kenneth McDonald; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Higher cardiac troponin is associated with worse outcomes in patients with acute heart failure. The significance of repeat measurements over hours remains unclear. We assessed whether a repeat measurement and the Δ between measurements of high‐sensitivity cardiac troponin I (hs‐cTnI) were associated with outcomes in hypervolemic patients with acute heart failure without acute coronary syndrome. Methods and Results We analyzed 582 individuals from AKINESIS (Acute Kidney Injury Neutrophil Gelatinase‐Associated Lipocalin Evaluation of Symptomatic Heart Failure Study) with hs‐cTnI measured ≤12 hours from admission and repeated ≤6 hours thereafter. Associations between hs‐cTnI levels and their Δ with short‐term (death, intensive care unit admission, receipt of inotropes, or positive pressure ventilation during hospitalization) and long‐term (death or heart failure readmission within 1 year) outcomes were assessed. The average age was 69±13 years, 62% were men, 65% were White, 46% had coronary artery disease, and 22% had chest pain. Median hs‐cTnI levels were 27 (interquartile range [IQR], 13–62) ng/L initially and 28 (IQR, 14–68) ng/L subsequently, with a Δ of 0 [IQR, −2 to 4] ng/L over 3.4±1 hours. Only the second measurement was associated with short‐term outcomes (odds ratio, 1.14 per 2‐fold higher [95% CI, 1.02–1.28]). Both individual measurements and the Δ were associated with long‐term outcomes (hazard ratios, 1.09, 1.12, and 1.16 for first, second, and Δ, respectively). Associated risk for the first and second measurements were not constant over the year but highest early after being measured and decreased over 1 year. Conclusions Repeat measurements of hs‐cTnI over hours can identify individuals with acute heart failure without acute coronary syndrome at risk for short‐ and long‐term outcomes.